Description of a new species of the genus Onconeura Andersen et Sæther (Diptera: Chironomidae) from Argentina with a cladistic analysis of the genus - Donato, Mariano; Siri, Augusto; Mauad, Melina (Zootaxa, 2012)
The male, female and immature stages of the new species Onconeura analiae from Argentina are described and figured. A parsimony analysis including the seven known species of the genus plus the new species, using a combined data set of continuous and qualitative characters, was conducted in order to assess the phylogenetic position of the new species and to give for the first time a phylogenetic hypothesis of the genus.